Combined effect of CO2 enrichment and foliar application of salicylic acid on the production and antioxidant activities of anthocyanin, flavonoids and isoflavonoids from ginger - Ghasemzadeh Ali; Jaafar Hawa ZE; Karimi Ehsan; Ibrahim Mohd (BMC, 2012)
Abstract Background The increase in atmospheric CO2 concentration caused by climate change and agricultural practices is likely to affect biota by producing changes in plant growth, allocation and chemical composition. This study was conducted to evaluate the combined effect of the application of salicylic acid (SA, at two levels: 0 and 10-3 M) and CO2 enrichment (at two levels: 400 and 800 μmol·mol−1) on the production and antioxidant activities of anthocyanin, flavonoids and isoflavonoids from two Malaysian ginger varieties, namely Halia Bentong and Halia Bara. Methods High-performance liquid chromatography (HPLC) with photodiode array detection and mass spectrometry was employed to identify and quantify the flavonoids and anthocyanins in the ginger extracts. The antioxidant activity of the leaf extracts was determined by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) and thiobarbituric acid (TBA) assays. The substrate specificity of chalcone synthase, the key enzyme for flavonoid biosynthesis, was investigated using the chalcone synthase (CHS) assay. Results CO2 levels of 800 μmol·mol−1 significantly increased anthocyanin, rutin, naringenin, myricetin, apigenin, fisetin and morin contents in ginger leaves. Meanwhile, the combined effect of SA and CO2 enrichment enhanced anthocyanin and flavonoid production compared with single treatment effects. High anthocyanin content was observed in H Bara leaves treated with elevated CO2 and SA. The highest chalcone synthase (CHS) activity was observed in plants treated with SA and CO2 enrichment. Plants not treated with SA and kept under ambient CO2 conditions showed the lowest CHS activity. The highest free radical scavenging activity corresponded to H Bara treated with SA under high CO2 conditions, while the lowest activity corresponded to H Bentong without SA treatment and under atmospheric CO2 levels. As the level of CO2 increased, the DPPH activity increased. Higher TBA activity was also recorded in the extracts of H Bara treated with SA and grown under high CO2 conditions. Conclusions The biological activities of both ginger varieties were enhanced when the plants were treated with SA and grown under elevated CO2 concentration. The increase in the production of anthocyanin and flavonoids in plants treated with SA could be attributed to the increase in CHS activity under high CO2 levels.